Characteristics Analysis of Electrostatic Generator - Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (IRAJ, 2017)
Due to the demand of the modern era, now electricity has become an important factor in every sector in our life. Almost everywhere the electromagnetic induction technique is used to generate the electrical power. Once upon a time, the electrostatic induction technique was used to generate the electrical power. Unfortunately, there is little information about the mathematical modeling and characteristics of static electricity generators. A Wimshurst electrostatic generator of disk diameter 34.0 cm has been designed and experimentally study the characteristics to find the optimized condition for maximum output power. From the results, it has been found that the generator has maximum performance when the conductor segment length about 30% of the diameter of the disk. The machine performance has intensely depended on the total surface area of the conducting material and slightly relied on the number of sectors/segments.